(untitled) (Altre Modernità, 2015)
L’èkphrasis come finestra tra due mondi. Su Nell’occhio di chi guarda, a cura di C. Bertoni, M. Fusillo, G. Simonetti (Roma, Donzelli, 2014, 199 pp., ISBN 978-88-6843-069-6) (pp. 449-452)